THE INFLUENCE OF ENVIRONMENTAL PERFORMANCE, ORGANIZATIONAL REPUTATION, ENVIRONMENTAL DISCLOSURE AND ENVIRONMENTAL STRATEGY ON BUSSINESS PERFORMANCE - Indra Saputra (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
This research aims to examine and analyze the influence of environmental performance, organizational reputation, environmental disclosure and environmental strategy on bussiness performance. In this research, the target population of this study was the manufacturing companies registered and participating in the Company Performance Rating Program (PROPER) issued by the Ministry of Environment in 2011-2016 with the sampling method using purposive sampling criteria, totaling 22 companies with 132 observations. Data analysis consists of descriptive and multiple regression linear regression. The results showed that the company’s reputation had a significant influence and environmental disclosure had a significant positive influence on business performance, while environmental performance and environmental strategy had no significant influence on business performance. Based on the evaluation, the environmental strategy will lead to company policies towards the application of an environmental management system. The current condition occurs that environmental strategy cannot make investors make decisions to buy shares because many other fundamental factors are the main consideration for investors in buying shares, meanwhile multitude of other factors and the main focus of the company as a business strategy is the fundamental reason that environmental strategy does not affect stock prices. This research is also expected to contribute conceptually to the company in determining further policies regarding the performance of a company to be more influenceive in its implementation.